Pengaruh Parental Phubbing dan Loneliness pada Remaja Awal di Sumatera Barat - Silvi Tri Wulandari; Maya Yasmin (Universitas Kristen Maranatha, 2026)
The increasing use of smartphones in family interactions has triggered the phenomenon of parental phubbing, which has the potential to disrupt the quality of emotional relationships and trigger feelings of loneliness in children. This study aims to determine the effect of parental phubbing on loneliness in early adolescents. Parental phubbing is the behavior of parents who divert their attention to smartphones while interacting with children, which has the potential to disrupt the quality of emotional relationships. This study used a quantitative approach with an ex post facto design involving 370 early adolescents aged 13-17 years in West Sumatra who were selected through a purposive sampling technique. The parental phubbing and loneliness instruments were developed based on theory and have been tested to be valid (item-total correlation ≥ 0.30) and reliable with Cronbach's Alpha values ​​of 0.766 and 0.972, respectively. Data were analyzed using normality tests and simple linear regression. The results showed that parental phubbing had a positive and significant effect on loneliness (β = 0.730; p < 0.001), indicating that increased parental phubbing tends to be followed by levels of loneliness in early adolescents. The coefficient of determination (R² = 0.380) indicates that 38% of the variation in loneliness can be explained by parental phubbing. This finding indicates that the higher the level of parental phubbing experienced by adolescents, the higher the level of loneliness they experience. These results emphasize the importance of quality parent-child interactions without digital distractions as a protective factor for adolescents' emotional well-being in the technological era.